Evolutionary insights and brief review of Loxodes Ehrenberg, 1830 (Ciliophora, Karyorelictea, Loxodidae) with description of a new species from Mexico - Méndez-Sánchez, Daniel; Mayén-Estrada, Rosaura; Ramírez-Corona, Fabiola (European journal of protistology, 2022)
Karyorelictids are a group of ciliates inhabiting marine and freshwater biotopes and possessing a non-dividing macronucleus. We describe a new freshwater species based on morphology and the 18S rRNA gene sequence data. Loxodes tziscaensis n. sp. can be easily distinguished from other Loxodes species by the arrangement of the nuclear apparatus and features of the buccal and somatic ciliature. The current proposed 18S rRNA phylogeny of Loxodes, including seven Loxodes species, shows two morphologically well-supported groups. Group A (L. rostrum, type species; L. vorax and L. tziscaensis n. sp.) includes species with a single nuclear group (two macronuclei and one micronucleus), in contrast to species of group B, which possess more than one nuclear group (L. striatus, L. magnus, L. kahli, L. penardi, and L. rex). We propose that the last common ancestor of Loxodes was a marine Remanella-like species possessing a single nuclear group. The division and differentiation of the micronucleus into a new macronucleus and the retention of the old macronuclei, independently of cell division, may have been two crucial processes during the evolution and diversification of Loxodes species with one nuclear group into species with multiple nuclear groups.
Keywords: Mexico; RNA ribozomální 18S; makronukleus; Protargol impregnation; Nuclear dualism; RNA, Ribosomal, 18S; Ciliophora; Loxodida; Phylogeny; fylogeneze; Non-dividing macronucleus; Mexiko; Macronucleus; Remanella